Insulin Sensitivity Determines Effects of Insulin and Meal Ingestion on Systemic Vascular Resistance in Healthy Subjects. (January 2016) - Woerdeman, Jorn; Meijer, Rick I.; Eringa, Etto C.; Hoekstra, Trynke; Smulders, Yvo. M.; Serné, Erik H.
Abstract: Objective: In addition to insulin's metabolic actions, insulin can dilate arterioles which increase blood flow to metabolically active tissues. This effect is blunted in insulin‐resistant subjects. Insulin's effect on SVR, determined by resistance arterioles, has, however, rarely been examined directly. We determined the effects of both hyperinsulinemia and a mixed meal on SVR and its relationship with insulin sensitivity. Methods: Thirty‐seven lean and obese women underwent a hyperinsulinemic‐euglycemic clamp, and 24 obese volunteers underwent a mixed‐meal test. SVR was assessed using CPP before and during hyperinsulinemia as well as before and 60 and 120 minutes after a meal. Results: SVR decreased significantly during hyperinsulinemia (−13%; p < 0.001) and after the meal (−11%; p < 0.001). Insulin decreased SVR more strongly in insulin‐sensitive individuals (standardized β : −0.44; p = 0.01). In addition, SVR at 60 minutes after meal ingestion was inversely related to the Matsuda index ( β : −0.39; p = 0.04) and the change in postprandial SVR was directly related to postprandial glycemia ( β : 0.53; p < 0.01). Conclusions: Hyperinsulinemia and meal ingestion decrease SVR, which is directly associated with metabolic insulin resistance. This suggests that resistance to insulin‐induced vasodilatation contributes to regulation of vascular resistance.